Opinion of teachers about the characteristics, special education needs and care of gifted students in Costa Rica. - Morales Chacón, Krissia (2009)
Opinion of teachers about the characteristics, special education needs and care of gifted students in Costa Rica. Few countries have the staff and facilities required for gifted students. I surveyed a sample of 279 teachers (preschool and primary) in the provinces of San José, Alajuela and Limón, Costa Rica about their knowledge of the ubject, characteristics of gifted learners and their ability to properly educate them. Their general view of the subject tends to coincide with that of experts but they also believe in several myths. Costa Rican teachers are not trained to deal properly with gifted students but believe that gifted students should be integrated into the regular educational system.